SFRP1 induces a stem cell phenotype in prostate cancer cells - Losada-García, Alberto; Salido-Guadarrama, Iván; Cortes-Ramirez, Sergio Alberto; Cruz-Burgos, Marian; Morales-Pacheco, Miguel; Vazquez-Santillan, Karla; Rodriguez-Martinez, Griselda; González-Ramírez, Imelda; Gonzalez-Covarrubias, Vanessa; Perez-Plascencia, Carlos; Rodríguez-Dorantes, Mauricio (Frontiers in Cell and Developmental Biology, 2023)
Prostate cancer (PCa) ranks second in incidence and sixth in deaths globally. The treatment of patients with castration-resistant prostate cancer (CRPC) continues to be a significant clinical problem. Emerging evidence suggests that prostate cancer progression toward castration resistance is associated with paracrine signals from the stroma. SFRP1 is one of the extracellular proteins that modulate the WNT pathway, and it has been identified as a mediator of stromal epithelium communication. The WNT pathway is involved in processes such as cell proliferation, differentiation, cell anchoring, apoptosis, and cell cycle regulation as well as the regulation of stem cell populations in the prostatic epithelium. In the present study, we explored the role of exogenous SFRP1 on the stem cell phenotype in prostate cancer. The results reveal that cancer stem cell markers are significantly increased by exogenous SFRP1 treatments, as well as the downstream target genes of the Wnt/-catenin pathway. The pluripotent transcription factors SOX2, NANOG and OCT4 were also up-regulated. Furthermore, SFRP1 promoted prostate cancer stem cell (PCSC) properties in vitro, including tumorsphere formation, migration, bicalutamide resistance, and decreased apoptosis. Taken together, our results indicate that SFRP1 participates in the paracrine signaling of epithelial cells, influencing them and positively regulating the stem cell phenotype through deregulation of the WNT/β-catenin pathway, which could contribute to disease progression and therapeutic failure. This research increases our molecular understanding of how CRPC progresses, which could help us find new ways to diagnose and treat the disease.